Preparation of pure methyl esters from corresponding alkali metal salts of carboxylic acids using carbon dioxide and methanol - Barve, Prashant P.; Kamble, Sanjay P.; Joshi, Jyeshtharaj B.; Gupte, Milind Y.; Kulkarni, Bhaskar D. (Industrial & Engineering Chemistry Research, 2012)
In the present article, for the first time, we report the synthesis of alkyl esters by direct esterification of alkali metal salts of carboxylic acids using carbon dioxide and alcohol. Methyl acetate, methyl benzoate, methyl salicylate, and methyl lactate have been synthesized by esterification of sodium acetate, sodium benzoate, sodium salicylate, and calcium lactate, respectively. The esterification reaction was carried out in a batch as well as in a semicontinuous mode of operation. A detailed study on the esterification of calcium lactate using methanol and carbon dioxide was carried out to record the effects of various operating parameters (like CO2 pressure, reaction temperature, moisture content in the calcium lactate, and initial concentrations of calcium lactate) on the esterification reaction. This synthesis route produces highly pure methyl lactate by direct esterification of calcium lactate with calcium carbonate as byproduct. The byproduct calcium carbonate was characterized for its crystallinity, surface area, and pore volume. The process route has the advantage that the synthesized byproduct can be recycled into the fermenter to make corresponding alkali metal lactate or the finely precipitated calcium carbonate can be used for various other applications. Thus, the recovery and recycle of alkali metal is possible providing a pollution free process for synthesis of pure methyl lactate.